Hiperedição do livro inédito Flôres e Espinhos de Eulálio Motta - Boaventura, Tainá Matos Lima Alves (2024)
This thesis, entitled Hyperedition of the unpublished book “Flôres e Espinhos” by Eulálio Motta, addresses the editing and study of the unpublished Flôres e Espinhos, which is part of the collection of the Bahia-based writer Eulálio de Miranda Motta, made available on the internet through the domain https://floreseespinhos.com.br/. It is understood that contemporary editorial practices encompass writers' archives as spaces where texts and paratexts interact and can be studied in their relationships, as each work carries with it a multitude of related contexts. Eulálio de Miranda Motta wrote for over six decades and kept various publishing projects, handwritten texts, typewritten documents, and printed works in his collection, including cleaned manuscripts and excerpts in the process of development, which give a laboratory-like quality to his personal archive. Among the publishing projects, Flôres e Espinhos stands out, outlined by the author in another manuscript notebook titled Caderno Lágrimas. In the project, the writer categorically indicates his editorial intention. This work aimed to epistemologically reflect on the directions of Philology in contemporary times as well as understand its praxis in the field of Digital Humanities in the editing of the aforementioned corpus. That is, Philology is no longer a field of study concerned solely with the restitution of texts; with the recovery of lost originals or the author's final texts. In this sense, editing texts that are part of a diverse documentary collection, as in this case, requires the philologist to adopt an interdisciplinary approach, which involves possible and necessary connections between various disciplinary fields, updating and revising their editorial practice, and also a redefinition of the notions of work and text, given that archived documents are interconnected by a network of meanings. The methodology combined philological studies and methods with research in the field of Digital Humanities. As a theoretical and methodological framework, the research was based on the preserved documentary sources in the collection and the studies developed by the researchers themselves; in the studies of Text Sociology, Philology, and Digital Humanities. The editorial project outlined by the author is discussed here, and the study is supported by interdisciplinary reflections that span the fields of Textual Criticism and Genetic Criticism; studies on Memory and Writers' Archives; and Philological Criticism.